Prevalence and Factors Associated with Non-adherence to Anti-Retroviral Therapy among Adult HIV Patients in the Catchment Ruhango Provincial Hospital - Uwingabire, Justine; Amos , Habimana (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Background: Antiretroviral Therapy (ART) significantly improves health and prolongs the lives of individuals living with HIV. However, maintaining optimal adherence to ART remains a critical challenge. This study aims to investigate the incidence and contributing factors of non-adherence to ART among HIV patients at Ruhango Provincial Hospital in Rwanda. Methods: This cross-sectional study utilized a quantitative approach, conducted from January 2 to March 30, 2024. A total of 414 respondents participated, comprising 273 females (65.9%) and 141 males (34.1%). The mean age was 39.17 years (SD = 10.9), with age groups as follows: under 30 (18.6%), 30-39 (37.2%), 40-49 (26.8%), and 50 and above (17.4%). Marital status varied, with 263 (63.5%) married. Educational attainment was predominantly primary level (96.4%). Results: Out of the respondents, 334 (81%) were adherent to ART, while 80 (19%) exhibited non-adherence, defined as less than 90% adherence. Notably, individuals aged 30 to 39 (OR = 0.341, p = 0.014) and 40 to 49 (OR = 0.370, p = 0.030) were less likely to be non-adherent compared to those aged 50 and above. Additionally, those with lower perceived threat regarding HIV were also less likely to be non-adherent (OR = 0.510, p = 0.030). Conclusion: The prevalence of non-adherence to ART in Ruhango District Hospital is 19%. To improve adherence, tailored education addressing misconceptions about ART is essential, particularly for older patients. Future qualitative studies could further elucidate the personal experiences and barriers affecting adherence.